PENGUATAN KARAKTER POSITIF SISWA SD MELALUI LITERASI DIGITAL DI ERA MEDIA SOSIAL - Al Kamil, Muhammad Nazimuddin; Mas'adi; AR, Muslim; Bulalong, Roberto Rolly (Education and Talent Development Center of Indonesia, 2025)
This community service activity aims to strengthen the positive character of elementary school students through digital literacy in the era of social media. The background of this activity is based on the increasing use of digital technology by elementary school children that has not been balanced with critical thinking skills, digital ethics, and social awareness, so that it risks triggering negative behavior such as bullying in the school environment and social media. This activity was carried out at SD Inpres 2 Talise, Palu City, using interactive lecture methods, group discussions, and educational video-based simulations. The evaluation was carried out using pre-test and post-test instruments to measure the increase in students' understanding of character values ​​and digital literacy. The results of the activity showed a significant increase in students' understanding, from 40% in the pre-test to 85% in the post-test. This activity shows that digital literacy can be an effective means of instilling positive character values, such as responsibility, empathy, and social media ethics. It is hoped that this activity can be an initial model for the development of a digital-based character strengthening program at the elementary school level